Metamorfoses da política de ajuste estrutural do banco mundial (1980-2014) - Mendes, João Márcio Pereira [UNESP] (FapUNIFESP (SciELO), 2017)
The article analyzes, focusing on Latin America, the World Bank's political agenda, implemented between 1980 and 2014, and based on the (neoliberal) structural adjustment of national economies. It is argued that this agenda has changed over the period, becoming increasingly politicized, comprehensive and intrusive in the involved States. There is evidence of coherence between the World Bank's political agenda and the sectoral and regional distribution of its loan portfolio.
Metamorphoses of the world bank's structural adjustment programme (1980-2014)
Keywords: Economic liberalism; Structural adjustment; World bank